PENDATAAN RAKYAT MISKIN UNTUK PROGRAM RASKIN BERBASIS WEB PADA NAGARI TANDIKAT KABUPATEN PADANG: DATA COLLECTION OF POOR PEOPLE FOR THE WEB-BASED RASKIN PROGRAM IN NAGARI TANDIKAT PADANG DISTRICT - Yahyan, Wahyuni; Fernandes, Efrian (Jurnal Manajemen Teknologi Informatika, 2024)
Poverty is one of the main problems faced in social life. With this, the Indonesian government took the initiative to help poor people, this aims to eradicate poverty in Indonesia. To expedite this program, villages are obliged to register poor people who deserve to receive direct assistance from the center. And the data obtained is deposited to the center. The method for collecting data on poor people usually must comply with the rules determined by the central government. However, Nagari Tandikat Padang Pariaman Regency in the Raskin data collection system still uses conventional methods by recording on paper, and the Raskin data archive often loses or is damaged. This results in time inefficiencies and inaccuracies in data archiving. This data collection process is one of the problems that arises in every village. Therefore, in this report an information system for processing data on poor people for the Raskin and Nagari Tandikat programs was created as the object of the Final Project. This information system is a data processing information system for poor people. This aims to build a Data Processing Information System for Poor People for the Poor Rice Program (Raskin). The research method used for this final assignment uses SDLC with UML system design tools. The programming language used to design the application is the PHP programming language with a MySql database.